WHAT IS DIGITAL TRANSFORMATION?. Issue 1 (3rd July 2021) - Tang, David
Abstract: Digital Transformation is a type of Business Transformation that is driven by emerging technologies. The potential for top line growth and bottom line savings of a Digital Transformation Program exceeds that of other types of Transformation initiatives. At its core, Digital Transformation is driven by the tangible shift in the role of the technology within an organization. No longer as purely a support function that enables business processes, technology is now capable of much more. Technology now allows for new, innovative business models (e.g. XaaS), drives sales growth, and can even be a source of Competitive Advantage. There are numerous emerging technology trends that drive Digital Transformation. Notable ones include Social Media, Mobility, Internet of Things (IoT), Cybersecurity, Big Data & Analytics, Cloud Computing, Robotic Process Automation (RPA), Artificial Intelligence (namely Machine Learning), Blockchain, and so forth. The applicability of technology is largely dependent on the industry and organization. With these technology trends, businesses are armed with the capability to fully digitize, transform, and grow their organizations. These technologies, in fact, mobilize 8 levers to Digital Transformation--spanning both Growth (business drivers) and Operational Improvement (business enablers).